The Effect of Monetary Variable Shocks on Indonesian Portfolio Investment - Fuddin, Muhammad Khoirul; Anindyntha, Firdha Aksari (Signifikan: Jurnal Ilmu Ekonomi, 2023)
Monetary variables can affect portfolio investment in the short or long term. The previous studies rarely discuss the effects of monetary variables in the long and short term on portfolio investment. This study looks at monetary indicators that affect investment portfolios in Indonesia. The methodology used in this research is to use the Vector Error Correction Model (VECM) to see the response of several variables in the short and long term. The findings suggest that monetary policy should pay special attention to Indonesia's money supply (M2) and savings to influence portfolio investment in the short term. The monetary policy transmission mechanism can use the money and expectation channels to optimize monetary variables to control investment. Meanwhile, in the long run, monetary policy portfolio investment control needs to pay attention to interest rates and savings and adjust to the set inflation target, which can be used in the interest rate channel.JEL Classification: E21, E22, E43, E51, E52 How to Cite:Fuddin, M. K., & Anindyntha, F. A., (2023). The Effect of Monetary Variable Shocks on Indonesian Portofolio Invesment. Signifikan: Jurnal Ilmu Ekonomi, 12(2), 307-326. https://doi.org/10.15408/sjie.v12i2.31525.